노인 불면에 대한 EFT 불면 치료 프로그램(EFT-1)의 효과 평가를 위한 예비적 연구 - 이정환; Jung Hwan Lee; 서현욱; Hyun Uk Suh; 정선용; Sun Yong Chung; 김종우; Jong Woo Kim (동의신경정신과학회지, 2011)
Objectives: The aim of this study was to evaluate the effects of EFT-I(EFT program for insomnia) for insomnia in the elderly as a preliminary study. Methods: This study was a single group pre-post comparative study that involved 10 elderly women(mean age=76.3±4.29), who visited a senior welfare center, complained of insomnia symptoms. Subjects received 8 sessions(twice a week for 4 weeks and 1 hour for each session) of EFT-I group training. Insomnia severity, depression, state anxiety, and life satisfaction of each subject were evaluated twice at pre and post of EFT-I. Korean Sleep Scale, Short form of Geriatric Depression Scale(SGDS), State-Trait Anxiety Inventory(STAI), and life satisfaction scale were used as evaluation tools. The data were analyzed using paired-samples T-test. Results: Insomnia severity, life satisfaction, depression, and state-anxiety were significantly improved by EFT-I. Conclusions: Result of this study showed that EFT-I can be a useful treatment program for elderly insomnia. Larger Clinical trials are needed to verify effect of EFT-I as a community based insomnia management program for the elderly.